The Effect Of An Educational Program On Developing Physical Concepts Among Kindergarten Children (Journal of the College of Basic Education, 2024)
The current research aims to identify an educational program in developing physical concepts for kindergarten children. The researchers prepared two tools, namely the physical concepts test and the physical concepts program for kindergarten children. They extracted the psychometric results of double validity and reliability. The study concluded that there were statistically significant differences between the average ranking The children of the experimental group copied in the pre- and post-test of applied patents, and there were no statistically significant differences between the average ranks of the children of the swab group on the physical concepts test in the pre- and post-test, and the presence of statistically significant differences between the average rank Kindergarten in testing physical concepts in the experimental and control groups in scientific experiments, and this difference is the experimental group